An investigation of lithium ion conductivity of copolymers based on P(AMPS‐co‐PEGMA). Issue 30 (4th April 2019) - Gunday, Seyda T.; Kamal, Aneeka Z.; Almessiere, Munirah A.; Çelik, Sevim Ü; Bozkurt, Ayhan
ABSTRACT: In this work, a series of novel lithium ion‐conducting copolymer electrolytes based on 2‐acrylamido‐2‐methyl‐1‐propane sulfonic acid (AMPS) and poly(ethyleneglycol) methacrylate (PEGMA) were produced and characterized. The copolymers were synthesized by free‐radical polymerization of the corresponding monomers with three different feed ratios to form P(AMPS‐co‐PEGMA)‐based electrolytes. After the polymerization, AMPS units of the copolymers were lithiated via ion exchange. The characterization of the electrolytes was done by 1 H‐NMR, FTIR, differential scanning calorimetry (DSC), thermogravimetric analysis, X‐ray diffraction, scanning electron microscopy (SEM), and impedance analyzer. The copolymers were thermal stable approximately to 200 °C. Single T g transitions in DSC curves verified the homogeneity as well as amorphous characteristics. SEM further confirmed the homogeneity of the electrolytes. The lithium ion conductivity of these new polymer electrolytes was studied by impedance dielectric impedance analyzer and the effect of PEGMA contents onto the ionic conductivity of these copolymer electrolytes were investigated. It was observed that the temperature dependence of ionic conductivity was interpreted over Vogel Tammann Fulcher model. The Li ion conductivity increased by PEGMA content and S3 has maximum conductivity of 3 × 10 −3 mS cm −1 at 100 °C. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47798. Abstract :